Atillum André, 1903 (Hymenoptera: Mutillidae) in Brazil: current and new geographic distribution records - André Luiz Marambaia; Greice Cristina Conceição da Silva; Ramon Lima Ramos; Matheus Eduardo Trindade-Santos; Roberto Alejandro Cambra; Kevin Andrew Williams (Revista Chilena de Entomología, 2023)
Popularly known as “witch ants” or “velvet ants”, mutillids are solitary ectoparasitoids wasps of immature insects. Atillum André, 1903, is a genus endemic to South America composed of 49 valid species. This study was motivated by the inconsistency of the available information, where, depending on the consulted bibliography, the number of Atillum species in Brazil varies. This contribution aims to reduce the knowledge gap on this genus, verifying the real number of species that comprise it and which actually inhabit Brazil. The specialized bibliography for Mutillidae and Atillum was consulted, in addition to carrying out an exhaustive consultation of the specialized bibliography. Additionally, to validate some of the records found, Atillum specimens deposited in the main collections that house this group were examined. As a result, records were found for ten Atillum species in Brazil, nine of which were confirmed as present in the country, and unpublished records of presence of Atillum and Atillum bucephalum (Perty, 1833) in four Brazilian states and eight municipalities located in the Northeastern region of the country.